PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS V SD NEGERI TULAP KABUPATEN MINAHASA - Lieke Stelda Rantung; Benyamin Salu (STKIP Subang, 2026)
This study aims to improve the science and social science (IPAS) learning outcomes of fifth-grade students at SD Negeri Tulap using the Project-Based Learning (PjBL) model. The research method employed is Classroom Action Research (CAR), conducted in two cycles. Eight fifth-grade students participated. Each cycle includes planning, action implementation, observation, and reflection. Data collection was carried out through observation, written tests, and document analysis. The results show a significant improvement in student learning mastery, from 37.5% in the pre-cycle to 62.5% in Cycle I, and reaching 87.5% in Cycle II. The class average score also increased from 58.75 in the pre-cycle to 72.50 in Cycle I and 84.37 in Cycle II, surpassing the minimum success indicator of 75%. These findings confirm that the PjBL model effectively enhances IPAS learning outcomes for fifth-grade students at SD Negeri Tulap.